Analysis of Student Policy Regarding the Implementation of Online Learning During the Covid-19 Pandemic - Nuraisyah Nuraisyah; Fadhliah; Donal Adrian (Postgraduate, University of Mataram, 2022)
The government, teachers, and all parties involved in education are committed to ensuring that students continue to learn, develop and have a good learning experience. During a pandemic, what is of concern is not whether online teaching and learning methods can provide quality education, but how universities can massively adopt online learning and ensure the implementation of online learning so that the teaching and learning process can take place. The research objective is to determine student satisfaction with the implementation of online learning (Covid-19 pandemic). The Cronbach alpha method of testing the reliability of the instrument produced. The results of the analysis of student satisfaction levels regarding online learning (the Covid-19 pandemic) are based on the four LORI components, namely planning, delivery, interaction, and evaluation, categorized as dissatisfied with online learning with a value of 35-45%.